'It made you think twice' – an interview study of women's perception of a web-based decision aid concerning screening and diagnostic testing for fetal anomalies. Issue 1 (December 2016) - Åhman, Annika; Sarkadi, Anna; Lindgren, Peter; Rubertsson, Christine
Abstract Background Enabling women to make informed decisions is a key objective in the guidelines governing prenatal screening and diagnostics. Despite efforts to provide information, research shows that women's choice of prenatal screening is often not based on informed decisions. The aim of this study was to investigate pregnant women's perceptions of the use of an interactive web-based DA, developed to initiate a process of reflection and deliberate decision-making concerning screening and testing for fetal anomalies. Methods A qualitative study was applied and individual interviews were conducted. Seventeen pregnant women attending antenatal healthcare in Uppsala County, Sweden, who had access to the decision aid were interviewed. Eleven opted to use the decision aid and six did not. Data were analysed by systematic text condensation. Results Women appreciated the decision aid, as it was easily accessible; moreover, they emphasised the importance of a reliable source. It helped them to clarify their own standpoints and engaged their partner in the decision-making process. Women described the decision aid as enhancing their awareness that participating in prenatal screening and diagnostics was a conscious choice. Those who chose not to use the web-based decision aid when offered reported that they already had sufficient knowledge. Conclusions The decision aid was able to initiate a process of deliberate decision-making in pregnant women as a result of their interaction with the tool. Access to a web-based decision aid tool can be valuable to expectant parents in making quality decisions regarding screening for fetal anomalies.